Museum Affairs during the Great Patriotic War (Historiographic Review) - Nina Konstantinovna Gurkina; Alexey Petrovich Isaev (Управленческое консультирование, 2018)
In the article, the problem of reflection in scientific literature of history of museum affairs during the Great Patriotic War is considered. The main attention is concentrated on the analysis of the works devoted to the main activities of the central and provincial museums during the military period.